AVALIAÇÃO DO CICLO DE VIDA DE UMA EDIFICAÇÃO RESIDENCIAL: ANÁLISE DOS IMPACTOS AMBIENTAIS INCORPORADOS PELOS MATERIAIS DE CONSTRUÇÃO - Pessoto, Lucas; Silva, Fernanda; Oliveira, Luciana; John, Vanderley (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The production of building materials plays an important role in determining the total environmental impact of buildings. In this study, the impact caused by the production of materials used in a popular building was assessed by means of Life Cycle Assessment. The Life Cycle Inventory was developed using ecoinvent version 3.3 and 16 impact categories were assessed, using four different LCIA methods (CED, CML, ReCiPe and Usetox). The main materials that contribute to the impact categories considered were presented, as well as which activities and substances emitted (or consumed) have the major contributions to environmental impacts. Most impact categories are related to fossil fuel consumption and corresponding emissions. Water consumption, resource depletion, particulate emission and land use are other relevant environmental impacts for construction. Some impact categories are related to activities far upstream the value chain, such as petroleum extraction. These differences must be considered when taking decisions for improving the environmental performance in the construction sector. Results also indicate a potential for simplification of the impact assessment step, that could help the adoption of LCA in construction sector.